Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sabun Colek Berbasis Ekonomi Rumah Tangga di Kelurahan Duren Jaya - Pramitasari , Anisa; Ningsih, Sari; Setyawati, Kiki; Aziza, Pretty Failasufa (P3M FIA UNKRIS, 2025)
This community service activity aimed to enhance the skills and economic independence of residents in Duren Jaya Subdistrict, East Bekasi, through a training program on producing dish soap (sabun colek) using low-cost but economically valuable materials. The main problem faced by the community was the lack of access to practical and affordable home-based business opportunities. The method used in this program was participatory training consisting of two stages: an educational session to introduce the benefits and business potential of sabun colek, followed by a hands-on demonstration of the production process. The results showed a significant improvement in participants’ knowledge and skills. After the training, 80% of participants were able to produce the soap independently, compared to only 10% before the activity. Some participants also began producing and selling the soap on their own, with a potential profit of IDR 200,000–400,000 per month. The success of this program was not only reflected in technical skills, but also in increased community participation, environmental support, and the availability of local raw materials. This activity demonstrates that a practical skills-based approach supported by interdisciplinary collaboration can effectively promote sustainable economic independence at the community level